U Sketch - Mai Abushamma; Rawan AbuZahra; Zainab Imran (My University, 2014)
Our project is a framework to facilitate building several applications converting the surfaces into interactive ones. Our system uses the Kinect and the WII technologies to convert the white board the teacher uses into interactive playground. The system receives input either from the traditional whiteboard pen (Flow-Master pen), or from the IR pen, then the system allows the user to deal with his input in an interactive way. The user draws certain shapes or even writes on the board then the webcam (which will be facing the white board) is used to capture the user written data, then the   Image processing techniques is used to extract and recognize these shapes and text. Moreover, we will use the Kinect depth camera to recognize the gestures of the user to interact with the recognized shapes (Resize, Move, Color, etc). And also we will use the WII IR sensor to receive commands from our IR pen to interact with the several elements on the board.  In this project we aim to develop a framework to facilitate the previously mentioned tasks in order to build applications utilizing the power of the Kinect and the WII easily, especially ones in the field of education and game. The project gains its importance from the variety of applications that can be applied, starting from games, educational apps (schools and universities) and architect tools which emphasize the element of interactivity. We aim to apply the technology more in our life. Also, we aim to combine fun and learning to help teachers to express ideas in a simple, fun ways.  We use the Kinect and the WII development environment and Image processing techniques to achieve our goal. The webcam gets the input image and send it to the image processing components to perform the analysis and recognize the shapes. Then the Kinect translates your body language into actions on the active shapes and the WII Mote provides the position of the IR pen. Projects in the same area exist, however our project focuses on facilitating writing interactive applications using the Kinect and WII.